Pharmacological FMRI in the development of new analgesic compounds. - Schweinhardt, P; Bountra, C; Tracey, I (2006)
Chronic pain is a major problem for the individual and for society. Despite a range of drugs being available to treat chronic pain, only inadequate pain relief can be achieved for many patients. There is therefore a need for the development of new analgesic compounds. The assessment of pain depends to date entirely on the subjective report of the patient, in contrast to many other clinical conditions where biomarkers that help determine the severity and stage of the disease enable the physician to monitor the course of the disease and treatment effects longitudinally. In this article, we illustrate that magnetic resonance-based imaging techniques have the potential to provide sensitive and specific biomarkers of the pain experience, as well as clarifying disease mechanisms. Functional magnetic resonance imaging (FMRI) is particularly suited to investigating the effects of pharmacological agents on pain processing within the human central nervous system. Combination of FMRI and drug administration is termed pharmacological FMRI (phFMRI). In addition to outlining several methodological considerations that have to be taken into account when performing phFMRI, we discuss phFMRI studies that have already used this technique to study the effects of analgesic compounds. These studies provide promising data for the use of phFMRI as sensitive tool in assessing a potential drug effect. Such pharmacodynamic readouts obtained early in the process of drug development would not only save the pharmaceutical industry substantial amounts of money, but would also avoid the unnecessary exposure of patients to molecules with limited or no therapeutic value. We are therefore optimistic that phFMRI will be used as a tool with high sensitivity and specificity for evaluating analgesic agents in early drug development and clinical studies.